Epstein-Barr Virus and Malaria Interactions: Immunology Perspective - Insani Budiningsih; Jaap M. Middeldorp; Yoes Prijatna Dachlan; Usman Hadi (Bogor Agricultural University, Indonesia, 2022)
Epstein-Barr Virus can cause various diseases, from acute inflammatory diseases such as fatal or chronic EBV infection, infectious mononucleosis as well as lymphoid and epithelial cancer, various autoimmune diseases, and also could interact with malaria. As EBV infects 95% of the world population, and more than 30% are infected with the protozoan parasite, with more than 500,000 deaths due to malaria cases. It is important to understand how EBV dysregulates the immune system, especially when the virus is interacting with other pathogens such as malaria parasites, causing more severe conditions in certain people like Burkitt Lymphoma. This review will be informative about the mechanism of how EBV interacts with malaria parasites and how it affects the immune system. Knowledge of various cytokines triggering the immune system which may provide links to control/minimize malaria disease severity.